The Effect of Composition Between Top Soil, Sinabung Volcanic Ash and Oil Palm Empty Fruit BunchesCompost as a Growing Mediumon the Growth of Deli Tobacco (Nicotiana tabacum L.) - Josef Tohap Leonardus Manalu; Jonis Ginting; Tengku Sabrina (Universitas Sumatera Utara, 2017)
The purpose of the study was to determine the effect of planting media consist of top soil, Sinabung volcanic ash and oil palm empty fruit bunches compost on the growth of Deli tobacco. The research was conducted at Balai Penelitian Tembakau Deli (BPTD) Sampali, Sub District Percut Sei Tuan, District Deli Serdang, Province North Sumatera with+ 15 m above sea level, began from May until July 2015. The research was arranged with a non-factorial randomized block design which was consisting of 6 treatments of top soil : volcanic ash : oil palm empty fruit bunches compost ratio that is M0 (15kg: 0kg: 0kg), M1 (12kg: 2,5kg: 0,5kg), M2 (12kg: 2kg: 1kg), M3 (12kg: 1,5kg: 1,5kg), M4 (12kg: 1kg: 2kg), M5 (12kg: 0,5kg: 2,5kg).The parameters observed were plant height, stem diameter, number of leaf, sand leaf lenght, feet leaf I length, sand leaf width, feet leaf I width, the thickness of sand leaf and the thickness leafI. The result showed that volcanic ash and oil palm empty fruit bunches compost significantly affected to plant height at 46 days after planting, stem diameter at 18-39 days after planting, number of leaf at 25-46 days after transplanting, sand leaf length, feet leaf I length, sand leaf width and feet leaf I width. Volcanic ash and straw compost did not significantly affected to plant height at 18-32 days after planting, stem diameter at 46 days after planting, number of leaf at 18 days after transplanting, the thickness of sand leaf and the thickness leaf I. Keywords: Deli tobacco, oil palm empty fruit bunches compost, volcanic ash